2022
DOI: 10.3390/biology11050639
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeny and Historical Biogeography of Veronica Subgenus Pentasepalae (Plantaginaceae): Evidence for Its Origin and Subsequent Dispersal

Abstract: Veronica subgenus Pentasepalae is the largest subgenus of Veronica in the Northern Hemisphere with approximately 80 species mainly from Southwest Asia. In order to reconstruct the phylogenetic relationships among the members of V. subgenus Pentasepalae and to test the “out of the Iranian plateau” hypothesis, we applied thorough taxonomic sampling, employing nuclear DNA (ITS) sequence data complimented with morphological studies and chromosome number counts. Several high or moderately supported clades are recon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…Fisch. only by its dense, compact habit, thinner petals and some other subtle morphometric differences, but the molecular studies confirmed that it is a distinct species ( Doostmohammadi et al 2022 ). However, V. kurdistanica is a unique species within V. kurdica complex differing from all others by its glandular indumentum, apart from other subtler differences mentioned above.…”
Section: Results and Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Fisch. only by its dense, compact habit, thinner petals and some other subtle morphometric differences, but the molecular studies confirmed that it is a distinct species ( Doostmohammadi et al 2022 ). However, V. kurdistanica is a unique species within V. kurdica complex differing from all others by its glandular indumentum, apart from other subtler differences mentioned above.…”
Section: Results and Discussionmentioning
confidence: 86%
“…6 ), by far the most species-rich subgenus in Iran, with many perennial, mountainous species. It has been demonstrated that this subgenus has probably originated in the Iranian plateau, with several relict and morphologically isolated species distributed at present along the Zagros and Alborz Mountains ( Doostmohammadi et al 2022 ).…”
Section: Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stereothrix (Fabaceae, Fabales, eudicots) [ 24 ] and Veronica subg. Pentasepalae (Plantaginaceae, Lamiales, eudicots) [ 25 ] from Eurasia were addressed. Whole plastome comparison revealed phylogenetic relationships in Crassula (Crassulaceae, Saxifragales, eudicots) [ 26 ] and in the family Magnoliaceae (Magnoliales, early branching angiosperms) [ 27 ].…”
mentioning
confidence: 99%